Secularism or theocracy - a study of the Malaysian constitution / Dr Shad Saleem Faruqr - Faruqr, Shad Saleem (Faculty of Administratron and Law, 2004)
During the last year or so an engaging debate has been raging about whether Malaysia is an Islamic or secular state. The non-Muslims of the country are adamant in their assertion that Malaysia's Constitution is and was, from the beginning, meant to provide a secular foundation. The opposition Muslim party, Partai Islam SeMalaysia (PAS) agrees with them that the Constitution is secular. But it says this in an accusatory tone and has made it clear that once in power it will amend the basic law to convert Malaysia into an Islamic state. The ruling Muslim party, United Malay National Organisation (UMNO), dismisses this proposal on the ground that Malaysia is already an Islamic state and, therefore, no constitutional amendments are needed. It rests its case on the fact that Muslims constitute the majority of the population. The constitutional monarchs at the federal and state levels are Muslims. The political executive, the civil service, the police, the army, the judiciary and the legislatures, while multi-racial, are under the control of Muslims. The federal and state Constitutions are replete with Islamic features. Islamic practices are gaining ground. Islamic economic and religious institutions thrive with state support.